Trace level determination of eleven nervous system-active pharmaceutical ingredients by switchable solvent-based liquid-phase microextraction and gas chromatography-mass spectrometry with matrix matching calibration strategy - Bozyigit, Gamze Dalgic; Ayyildiz, Merve Firat; Chormey, Dotse Selali; Engin, Guleda Onkal; Bakirdere, Sezgin (SPRINGER, 2022)
This study utilized switchable solvent liquid-phase microextraction (SS-LPME) to enrich eleven nervous system active pharmaceutical ingredients (APIs) from aqueous samples for their determination at trace levels by gas chromatography mass spectrometry. The analytes selected for the study included APIs utilized in antidepressant, antipsychotic, antiepileptic, and anti-dementia drugs. Parameters of the microextraction method including switchable solvent volume, concentration and volume of the trigger agent (sodium hydroxide), and sample agitation period were optimized univariately to boost extraction efficiency. Under the optimum conditions, the detection limits calculated for the analytes were in the range of 0.20-8.0 ng/mL, and repeatability for six replicate measurements as indicated by percent relative standard deviation values were below 10%. Matrix matching calibration strategy was used to enhance quantification accuracy for the analytes. The percent recovery results calculated for the eleven analytes ranged between 86 and 117%.
Keywords: APIs; GC-MS; Nervous system; SS-LPME; Wastewater; HF-LPME; WATER; Environmental Sciences & Ecology